La Digital diplomacy: what role in resolving international conflicts? - RIFKI, LALLA MINA (Revue Internationale du Chercheur, 2025)
Digital diplomacy has emerged as a fundamental instrument in contemporary international relations, particularly in conflict resolution. This study provides an in-depth analysis of the impact and effectiveness of this new form of diplomacy in promoting international peace and stability.Drawing on a plural theoretical framework combining realist and constructivist approaches with a geopolitical perspective, this research examines the institutional and operational transformations brought about by diplomatic digitalization. Through empirical analysis of cases such as the Iranian crisis and Colombian peace negotiations, the study demonstrates both the significant potential and inherent limitations of digital diplomatic tools.The findings suggest the necessity of a hybrid approach, integrating digital innovations with traditional diplomatic methods. The study concludes by exploring future developments in diplomacy, particularly the integration of artificial intelligence and immersive technologies in diplomatic practices.